FAKTOR YANG MEMPENGARUHI TINGKAT KEPUASAN KONSUMEN PADA PRODUK KECANTIKAN ISLAMI WARDAH - Sari, Delfia Permata; ', Suarman; ', RM. Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Based on Pre-survey, data obtained after conducting a survey to 10 consumers who have used the product Wardah concluded that 8 of 10 consumers are feeling very satisfied after using the product Wardah, on point of views are the product quality, price and customer service. The goal of this research is to determine the factors that affect the level of customer satisfaction in beauty products islami Wardah. The population in this study is a student at the Faculty of Education, University of Riau that using products Wardah. The number of samples in this study is 50 students with accendential sampling techniques. Data analysis technique that used is the Importance Performance Analysis (IPA). The results of this research that among these three factors that affect the level of customer satisfaction in beauty products Wardah, such as: a factor of the quality of services, aspects that affect customer satisfaction on the quality of service is responsiveness, direct evidence and the good service.Keywords: service, costumer satisfaction